An Analysis of Language Style Used in Captions and Comments on Tiktok Account - Febrianti, Iin; Sahril, Sahril; Iskandar, Iskandar (State University of Makassar, 2025)
As social beings, we interact with others. One form of interaction is communicating. In communicating, we need language so that we can convey our ideas, thoughts, desires, intentions and goals to others. Language makes it easier for one to understand information, so that complex problems such as misunderstandings can be prevented with good interpersonal communication.The circumstances encountered can have an impact on the variations of language employed. Everyone will use a different style to express feelings of sadness, joy, anger, boredom or even interest. Like wise with someone who speaks or writes something to people they know and their best friends, children will speak in a different style. The focus of this research is to explore the variation of language used in the captions and comments in the Andrea's Tiktok account. The researchers used qualitative research methods in this research. To collect data, researchers read and then add the selected content to the favorite section for identification. There are 36 extracts collected from the selected contents on Andrea's Tiktok account. The manner of language used by Andrea and his followers was discussed based on the theory of Martin Joos (1976). In this case, the researchers found that Andrea used several language styles in writing captions and also comments by her followers. The language styles used are: Frozen Style, Formal Style, Consultative Style, Casual or informal Style and intimate Style. In other words, we need a variation of language in communication with the aim of making listeners or readers know how we convey things and can make a difference about people from their language style so that everyone has their own unique language style depending on their accents, the language of their surroundings or possibly influenced by their friends or family.Keywords : Communication, Language style, Frozen style, Formal style, Consultative style